Зниження рівня окислів азоту при спалювані низькосортних палив - Мисак, Й.; Гнатишин, Я.; Крук, В.; Близнюк, В. (Видавництво Національного університету «Львівська політехніка», 2003)
It is considered a method of decrease(reduction) of formation(education) of oxides of nitrogen in the camera of recirculation smoke gases. For this purpose in a partition two-chamber topka it is stipulated two apertures.